KAP of influenza, streptococcal pneumonia, and herpes zoster among community-dwelling older adults with chronic diseases in Nanjing city: a cross-sectional survey - Zhengkai SHEN; Siyu TIAN; Zhiyong WANG; Wenjing ZHU; Lirong DONG; Jinshui XU (Zhongguo gonggong weisheng)
ObjectiveTo understand the knowledge, attitudes, and practices (KAP) related to influenza, streptococcal pneumonia, herpes zoster and their vaccines among community residents aged 60 years and older with hypertension or type 2 diabetes in Nanjing city, Jiangsu province, to provide a basis for better community health management services. MethodsThe study population consisted of 7 074 residents aged 60 years and older with hypertension or type 2 diabetes who were recruited through random cluster sampling from 32 community health centers in three districts of Nanjing city, Jiangsu province. Face-to-face interviews were conducted with participants using a self-developed questionnaire in February – March 2023. Chi-square test and one-way analysis of variance (ANOVA) were used for statistical analysis. ResultsOf the 6 790 (96% of all residents surveyed) participants with valid responses, only 2 260 (33.3%) had adequate knowledge (correctly answering 8 out of 12 questions about the three diseases), and χ2 test results showed that participants aged 60 – 70 years and those with higher levels of education had significantly higher knowledge (both P < 0.05). Trend χ2 test showed that there was a linear correlation between education and knowledge level (P < 0.05). One-way ANOVA results showed that participants who were female, aged 80 years and above, and had basic medical insurance were more concerned about the three diseases, while those with higher education level had higher acceptance of vaccines/vaccination against the three diseases (P < 0.05). Only 7% of the participants disagreed with the statement "very concerned about side effects of the vaccines" and 58.3% were more likely to accept vaccination recommendations from doctors. There were significant differences in behavioral prevention scores for the three diseases among participants with different levels of education and health insurance status (P < 0.05), with higher behavioral scores among participants with higher education or basic health insurance. Only 22.9% of participants reported that they had received out-of-pocket vaccinations for the three diseases. ConclusionThe KAP related to influenza, streptococcal pneumonia, herpes zoster and their vaccines were at a low level among community-dwelling older adults with hypertension of type 2 diabetes in Nanjing city.